(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, special attention is paid to the state and development of the tourism industry in Uzbekistan, the relevance of the development of domestic tourism and tourism infrastructure sectors of the country. It is also an industry that has become one of the most important in the process of implementing the state policy and strategy for the development of the tourism sector.